BUSINESS STUDENTS’ ATTITUDE TOWARDS BUSINESS ETHICS IN PAKISTAN - Rizvi, Shaheer; Tanveer, Muhammad Asif; Saleem, Umer; Latif, Moaaz (European Scientific Journal, ESJ, 2012)
Social responsibility of business and impact of business on society has got some immense importance during last decade. In this prospective, business students who are future leaders, entrepreneurs, managers, and employees- can play vital role in the development of better society. This study explored the ethical orientation of business student in Pakistan. It inspects whether dissimilarities in student’s demographic and personal characteristics have any attitude regarding business ethics. Attitude towards business ethic questioner (ATBEQ) is adopted as a measurement scale. Sample size of 102 students was taken from management sciences department, The Islamia University of Bahawalpur, and descriptive statistics and t-test employed. The results showed that there are some differences in the attitude of male and female students. Female responded more positive attitude than male. It also reflected that level of study and knowledge about business ethics shape positive attitude for social and moral obligation. Study recommended that more practical and conceptual framework of knowledge and studies should be included in the curricula.